Influence of information and communication technologies on the competitive advantage of micro-enterprises – Huancayo - Roberto Líder Churampi-Cangalaya; Miguel Fernando Inga-Ávila; Jesús Ulloa Ninahuaman; Enrique Mendoza Caballero; José Luis Inga-Ávila; Efraín Núñez Villazana; Madelyn Apardo Quispe (International Journal of Data and Network Science)
In a context where ICTs are indispensable elements for the development of business activities, it is necessary to know their influence on the internal improvement of processes. This research seeks to establish the influence of ICTs on the competitive advantage of micro-enterprises in Huancayo 2024. Research developed under a basic type study, has a quantitative approach with a correlational and cross-sectional level, the sample was made up of 59 entrepreneurs in the bakery sector in the province of Huancayo. Data analysis and processing was carried out using structural equations based on PLS. The study obtained the following results: a Sperman 's Rho correlation coefficient of 0.821 with a significance level of ,000 which shows a high and positive degree of influence between ICTs and competitive advantage as well as its different dimensions Level of use, alignment of use and training; Likewise, the general hypothesis is accepted, which establishes that there is a significant relationship between Information and Communication Technology ( ICTs ) and the competitive advantage in SMEs in the pastry sector - Huancayo 2024.